THE COMPREHENSIVE APPROACH IN TRAINING PROFESSIONAL FOREIGN LANGUAGE FOR STUDENTS OF INTERNATIONAL RELATIONS - Yusupova, Alexandra Yu.; Tyabina, Diana V.; Kolpakova, Svetlana G. (Gênero & Direito, 2019)
The initial professional language training of future specialists in the sphere of International Relations includes enriching the vocabulary through learning the terms of physical and political geography. The study of specific terminology is the task of a foreign language integrated learning course, within the framework of which students can obtain knowledge of both the naming (foreign language) and the substantive (subjective) aspects of the profile conceptual apparatus. To implement the integrated language course, the present study used a comprehensive approach and a method of a three-step lesson. These methods allowed the use of an individualized approach to deal with significant volumes of vocabulary, its semantic and grammatical features.